KELAYAKAN SISTEM EVAKUASI KAWASAN RAWAN BENCANA LETUSAN GUNUNG MERAPI DI KABUPATEN SLEMAN - Dicky Setya Adi W; Kusumastuti Kusumastuti; Isti Andini (Universitas Sebelas Maret Surakarta, 2016)
Evacuation system in Mount Merapi eruption area consist of evacuation component, such early warning system, meeting point, evacuation lane, evacuation route, barrack, communication and transportation. The role of the goverment is to give services for refugees who live in scenario evacuation area. But there are some constrains, for example damaged road, evacuation lane crossover the bridge, people don’t heard the early warning system and high density of barracks. Based on those phenomenons, this research objected is to measure the feasibility of Mount Merapi evacuation system in Sleman district by using qualitative and quantitative method. The results of this research, some of evacuation systems don’t have perfect score. Early warning system has score 49%, meeting point score 96,2%, evacuation lane 88,7%, evacuation route 100%, barracks 60,7%, transportation and communication 51,8%. From that components, the average score is 75% which means the system of evacuation in Mount Merapi Eruption Area not feasible yet.